Knowledge and Attitude of Antibiotic Use among Public in Rural Area of Cempaka, Banjarbaru, South Kalimantan - Nurul Mardiati; Rahmayanti Fitriah; Nadia Wahyu Artati; Wika Tiarawati; Muhammad Zaini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The high intensity of antibiotics relatively uses causes various problems for health, especially bacterial resistance to antibiotics. Lack of public knowledge about the rationale of antibiotics is a factor that can trigger bacterial resistance to antibiotics. This study aims to assess the public's knowledge and attitudes towards antibiotic use in rural areas Cempaka, Banjarbaru, South Kalimantan. This was a descriptive cross-sectional survey method in which closed-ended questionnaires were distributed to 380 rural residents in the village of Cempaka proportional stratified random sampling technique. Data analysis used univariate and bivariate with the Chi-Square statistical test method. In conclusion, the rural residents demonstrated moderate knowledge (83.2%) and a positive attitude towards antibiotic use (97.4%). There is no significant association between both knowledge level and of antibiotics on the attitude towards antibiotic use.